The Leadership of Administrators That Affects Team Work in School Organization of Schools Under The Samut Prakan Primary Educational Service Area Office 1 - Thongsri , Kanyapak; Sanitlou, Nipitpols (Mahachula Academic Journal, 2024)
This objectives of the research article are (1) to study the leadership of administrators in school organizations under the Samut Prakan Primary Educational Service Area Office, District 1 (2) teamwork in school organizations under the Samut Prakan Primary Educational Service Area Office, District 1 (3) Leadership of administrators that affects teamwork in school organizations under the Samut Prakan Primary Educational Service Area Office 1 The sample group used in this research consisted of Teachers working in educational institutions Under the Samut Prakan Primary Educational Service Area Office, Area 1, academic year 2022, the number of students was 327. The sample size was determined using the sample comparison table. The research tool was a questionnaire on the leadership level of the people. Management that affects teamwork in school organizations under the Samut Prakan Primary Educational Service Area Office 1It has the characteristics of a 5-level estimation scale of Thanin Silcharu, which has a confidence value for the whole version equal to 0.82. Statistics used in data analysis include percentage (%), mean (x ̅), standard deviation (S.D.). Alpha coefficient analysis of variance Pearson’s correlation coefficient and stepwise multiple regression analysis